The theory of maximal social welfare feasible coalition - Boongasame, Laor; Boonjing, Veera; Leung, Ho Fung (My University, 2007)
This paper proposes a new theory for forming a maximumvalue-cooperation coalition known as the Maximal Social Welfare Feasible Coalition. This theory can give such solution because it does not assume that each player requesting to join a coalition knows information of other players. However, all players' private information requesting to join the coalition is known by an honest coordinator. This allows the coordinator to select a coalition structure with maximal value of cooperation among successful players so as they get at least at their required minimum values. Not only this maximal value is shown to be equal to or larger than the value of a core coalition but also the value allocation is shown to be Pareto optimal. © Springer-Verlag Berlin Heidelberg 2007.
Keywords: Coalition formation; Cooperative game theory; Group buying; Pareto optimally; The core